Science Attitude on Environmental Conservation of Thai and Indonesian Novice Science Teacher Students - Nuangchalerm, Prasart; El Islami, R. Ahmad Zaky; Prasertsang, Parichart (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
World is now rapidly changed by human activities that effect to environment and all of us. Process and product of science and technology transformed our knowledge and way of life to modern society. Local knowledge and scientific knowledge are related to means of co-learning space. Science education should play its importance roles and goals to use science and technology for sustainable development. The aim of this study was to compare Thai and Indonesian novice science teacher students in science attitude on environmental conservation based on local wisdom of Baduy’s society. The subjects were 95 of Thai and 71 of Indonesian novice science teacher students. They were asked indigenous knowledge for preserving natural resources and community practices. Attitude on environmental conservation is explored and explained through the scientific literacy test. The results showed that mean score of Thai novice science teacher students had better than Indonesian movice science teacher students and significantly differences at .05 level of statistics. Need future studies which concern to improve science attitude and scientific literacy in the teacher education program.